Evaluation of Quality of Life and Affecting Factors Among Nurses Working in Elazig City Center Hospitals - Önal, Fulya; Oguzoncul, Ayse Ferdane; Tuncer, Kevser (My University, 2023)
Aim: The aim of this study is to examine the life quality of nurses, who cover a wide range of healthcare professionals, according to various variables. Methods: The universe of the cross-sectional study consisted of 1082 nurses working in hospitals. The sample of study composed of 723 nurses (66.8%). We evaluated data in the SPSS-22 program. Percentage, mean, t-test, Chi-square test, and one-way analysis of variance (ANOVA) were used according to the characteristics of the variables. p <0.05 was considered to be statistically significant. Results: 68.6% of the study group were women, 56.8% were married, and 50.1% had completed their undergraduate education. When Short Form-36 (SF-36) was compared subscale groups according to smoking status, a significant relationship was found in others except for the role emotional (p<0.05). There was a significant difference in all sub-items of SF-36 by age groups (p<0.05). At all subscales, the scores of singles and men were significantly higher (p<0.05). As the year worked increased in the physical functioning category, the quality of life scores was falling. Conclusions: As the year worked, the number of children and income increased, the quality of life scores were falling. The quality of life of nurses should be increased by improving working hours and conditions.
Keywords: Quality of Life; Nurse; Hospital